2016
DOI: 10.15252/embj.201694253
|View full text |Cite
|
Sign up to set email alerts
|

CLPP coordinates mitoribosomal assembly through the regulation of ERAL1 levels

Abstract: Despite being one of the most studied proteases in bacteria, very little is known about the role of ClpXP in mitochondria. We now present evidence that mammalian CLPP has an essential role in determining the rate of mitochondrial protein synthesis by regulating the level of mitoribosome assembly. Through a proteomic approach and the use of a catalytically inactive CLPP, we produced the first comprehensive list of possible mammalian ClpXP substrates involved in the regulation of mitochondrial translation, oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
213
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(237 citation statements)
references
References 47 publications
18
213
1
5
Order By: Relevance
“…CLPP encodes a mitochondrial ATP-dependent endopeptidase34 and CLPP-deficiency causes Perrault syndrome3536 (OMIM #601119) which is overlapping with the clinical presentation of the patient investigated here including microcephaly, deafness and severe psychomotor retardation (Supplementary Note 1). Moreover, a study recently showed that Clpp−/− mice are deficient for complex IV expression37, in line with complex IV deficiency of this patient (Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 79%
“…CLPP encodes a mitochondrial ATP-dependent endopeptidase34 and CLPP-deficiency causes Perrault syndrome3536 (OMIM #601119) which is overlapping with the clinical presentation of the patient investigated here including microcephaly, deafness and severe psychomotor retardation (Supplementary Note 1). Moreover, a study recently showed that Clpp−/− mice are deficient for complex IV expression37, in line with complex IV deficiency of this patient (Supplementary Fig. 5).…”
Section: Resultssupporting
confidence: 79%
“…The acyl‐CoA dehydrogenases differ in their specificity for very long‐ (VLCAD), long‐ (LCAD), medium‐ (MCAD), and short‐chain acyl‐CoAs (SCAD) . Although both MCAD and SCAD were detected as possible CLPP substrates in the previous screen , the overall striking upregulation of VLCAD suggests it to be a likely CLPP substrate (Fig B and C). The strongest upregulation of VLCAD levels was observed in EWAT (25‐fold) in addition to low LCAD and high MCAD levels (Fig C).…”
Section: Resultsmentioning
confidence: 89%
“…To unravel the in vivo function of CLPP in mammals, we recently generated whole-body CLPP-deficient mice (Clpp À/À ) [6]. Although CLPP function seems to be necessary in some critical period during development [6], the deficiency did not influence the postnatal life span, as no changes in the median or maximal survival for both sexes of Clpp À/À mice were detected ( Fig EV1A), in contrast to a previous study on a different CLPP-deficient model that reported a strong reduction in life span to about 1 year of age [8]. Possible reasons that might account for the discrepancy could be the different techniques used to generate the CLPP-deficient mice (gene trapping versus gene targeting) or differences in the hygienic status of the animal facilities.…”
Section: Resultsmentioning
confidence: 99%
“…ClpP deletion was shown to ameliorate the deleterious consequences of dysregulating mitochondrial translation induced by deleting mitochondrial aspartyl aminoacyl‐tRNA synthetase. As a consequence, these results demonstrated that ClpP activity is actively involved in regulating mitochondrial translation and adaptation to metabolic demands, discarding that ClpP is exclusively acting as a disposal unit to degrade dysfunctional proteins and/or regulating the mitochondrial unfolded protein response in mammals .…”
Section: The Role Of the Mitochondrial Protease Clpp In Obesity And Imentioning
confidence: 94%